2010
DOI: 10.4104/pcrj.2010.00086
|View full text |Cite
|
Sign up to set email alerts
|

Developing and testing search strategies to identify patients with active seasonal allergic rhinitis in general practice

Abstract: Aim: We sought to assess the accuracy of different search terms to identify individuals with active seasonal allergic rhinitis (SAR) in general practice.Methods: A reference search strategy was developed to identify patients with active SAR. This was applied through inspection of electronic health records of patients aged 15-45 years in a 10% random sample of a general practice database. Searches used Read codes and medication relating to SAR. Sensitivity, specificity, and positive and negative predictive valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…There are other examples of searches using Read codes that had low sensitivities. In studies of electronic health records, fewer than two-thirds of patients with diabetes mellitus were correctly identified using the specific code ‘C10 Diabetes mellitus,’ and only 17 % of patients with active seasonal allergic rhinitis could be identified on the basis of a specific Read code [ 10 , 11 ]. Furthermore, the practice of recording body mass index rather than a diagnosis of obesity resulted in only 2.1 % of patients with obesity being identified using a specific Read code [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other examples of searches using Read codes that had low sensitivities. In studies of electronic health records, fewer than two-thirds of patients with diabetes mellitus were correctly identified using the specific code ‘C10 Diabetes mellitus,’ and only 17 % of patients with active seasonal allergic rhinitis could be identified on the basis of a specific Read code [ 10 , 11 ]. Furthermore, the practice of recording body mass index rather than a diagnosis of obesity resulted in only 2.1 % of patients with obesity being identified using a specific Read code [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…THIN also contains details of referrals to specialists, and diagnoses associated with these consultations may be entered retrospectively by PCPs, using Read codes or free-text comments. With the availability of multiple Read codes, there can be considerable variation in how PCPs record information, and previous studies have identified the need for bespoke search strategies that reflect the clinical and coding definitions in use [ 10 ]. For example, a study of the use of Read codes in diabetes mellitus management revealed that 25 different codes were reported in the 17 practices examined [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…We defined current seasonal allergic rhinitis by the presence of a documented clinician diagnosis in the patient’s electronic health record and any evidence of treatment(s) used for seasonal allergic rhinitis in the last 2 years. 21 Patients who fulfilled these criteria were invited to take part in the trial via a letter from the practice, which included a participant information sheet, consent form and reply envelope for return directly to the research team.…”
Section: Methodsmentioning
confidence: 99%
“…The definition of who is considered an asthma patient varies greatly in the literature (41). These definitions are currently being refined to define patients in general practice with active asthma and SAR (42).…”
Section: General Practice (Wlgp)mentioning
confidence: 99%